Parents’ COVID-19 stressors and associations with self-rated health, symptoms of mental health problems, and substance use: a cross-sectional study - Janique Fortier; Samantha Salmon; Tamara Taillieu; Ashley Stewart-Tufescu; Harriet L. MacMillan; Lil Tonmyr; Andrea Gonzalez; Melissa Kimber; Leslie Roos; Jitender Sareen; Tracie O. Afifi (FACETS)
The aim of this study was to understand associations between pandemic stressors and parents’ self-rated physical and mental health; symptoms of mental health problems, and at-risk substance use problems. Data were collected from February 2022 to March 2022 as part of Wave 2 of the Well-being and Experiences Study in Manitoba, Canada (n = 749). Stressors frequently identified since the onset of the pandemic included inability to spend time with family and friends, worry about getting coronavirus disease-2019 (COVID-19), and travel restrictions. In the past month, the most frequently identified stressors were worry about getting COVID-19, travel restrictions, public health restrictions, and worry about the future. The stressors with the greatest number of associations with worse health outcomes included: job loss or financial burden; feeling lonely or isolated; disrupted or poor sleep; uncertainty about the future; accessing health care for any reason; increased conflict in relationships; cancellation of surgeries, caregiving for children; and inability to spend time with family. Understanding the COVID-19 stressors that were associated with health and substance problems can inform clinical approaches to respond to pandemic-related problems, as well as public health preparedness to mitigate declines in parents’ health and well-being in the context of future pandemics.